Effect of Vd-Doping on Dielectric, Magnetic and Gas Sensing Properties of Nickel Ferrite Nanoparticles - Casagrande-Denardin, J (Springer, 2020)
Pristine and vanadium-doped nickel ferrite (NiFe2O4) nanoparticles (NPs) were prepared by a chemical co-precipitation method. They were characterized by X-ray diffraction, scanning electron microscopy and X-ray photoelectron spectroscopy to explore their crystallinity, morphology and chemical states. Dielectric constant and dielectric loss properties were studied as a function of frequency and temperature and it was found that V-doping resulted in the enhancement of the dielectric properties. Both pristine and V-doped ferrites showed superparamagnetic nature and zero coercivity and retentivity. However, the saturation magnetization was decreased after V-doping, suggesting presence of superexchange interaction between A–B sites. Both pristine and V-doped NiFe2O4 NPs were also used for NO sensing studies and it was revealed that V-doped gas sensor revealed a better sensing performance (response of 5 s and sensitivity of 43 to 200 ppm NO gas) than pristine one (response of 9 s and sensitivity of 37 to 200 ppm NO gas). © 2020, Springer Science+Business Media, LLC, part of Springer Nature.